KONSEP PENGUATAN PERAN STEWARDSHIP - Irma Safni (Faculty of Economics and Business Mulawarman University, 2015)
Today, many companies have conducted various CSR activities as initiatives to give back to the society. Charity is one of an important part of CSR. However, in some cases charity is sometimes carried out badly or less sustainability. Indeed charitable giving may even distract from finding best solution which might make people become more dependence to company. If that is so, then the effort should be better devoted to empowering communities by which CSR activities could be controlled effectively and efficiently. Community empowerment might be more likely to focus on enhancing and building people’s capacity that implies their community ownership in the region. That’s because CSR aims to develop community by empowering it. In the end, it’s hoped that people could synergize with company’s missions and act as partners that need and complete each other. Keywords: Community Empowerment.